Strategi Penguatan Tata Kelola Sumber Daya Manuasia Bidang Kebencanaan : Analisis Pasca Restrukturisasi dan Optimalisasi Pusat Pembinaan Jabatan Fungsional BNPB 2025 - Anggita Wulandari; Asropi Asropi (Journal Of Administration and Educational Management (ALIGNMENT), 2026)
This study aims to analyze strategies for strengthening human resource governance in the disaster sector following organizational restructuring through the optimization of the BNPB Functional Position Development Center (Pusbin JF) in 2025 to support increased capacity of disaster personnel. The research method used was a qualitative study with a Systematic Literature Review (SLR) approach through a literature search in the Google Scholar and ScienceDirect databases. The selection process was conducted based on inclusion and exclusion criteria, resulting in 16 relevant scientific articles for systematic analysis. The results indicate that strengthening human resource governance in disaster management requires four main strategies: the application of Training Needs Analysis (TNA) as the basis for developing a competency-based curriculum; the implementation of Agile Human Resource Management to increase organizational flexibility and talent management; the modernization of the training system through digitalization and tactical simulations based on field needs; and the implementation of dynamic governance supported by the operationalization of Pusbin JF as a development unit responsible for competency standardization, credit score management, performance evaluation, and career development for functional positions. This study also yielded three strategic recommendations: institutional strengthening through accelerated operationalization of the Disaster Management Center (Pusbin JF) and the implementation of knowledge management; modernization of the TNA-based training system and 360-degree evaluation; and synchronization of welfare through accelerated regulation of functional allowances and strengthening the talent retention system. The study's conclusions indicate that the success of strengthening disaster human resource governance at the National Disaster Management Agency (BNPB) depends on the synergy between institutional strengthening, competency development based on organizational needs, and support for staff welfare, thereby achieving a professional, adaptive, and sustainable disaster management system.   Keywords: Agile Human Resource Management, Dynamic Governance, Disaster Functional Positions, Human Resources, Training Needs Analysis